REAKSI PASAR MODAL INDONESIA TERHADAP PENGUMUMAN INDONESIA SEBAGAI NEGARA MAJU - Ely Damayanti; Rahayu Dwi Larasati; Kharis Fadlullah Hana (POINT: Jurnal Ekonomi dan Manajemen, 2020)
The purpose of this tdudy is to analyze the differences in abnormal return before and after the announcement of Indonesia as a developed country on the LQ45 stock index. This study uses a purposive sampling method with a sample of 45 companies. The data used are secondary data taken from the official website of the Indonesia Stock Exchange, www.idx.co.id. Tests were carried out using paired sample t test with a 15 day event window period. That is, seven days before the event day and sevend days after the event day. The result of statistical analysys shows that there is no significant average abnormal return and after the announcement of Indonesia as a developed country. This means that the market reaction, is largely insignificant, result in a statistically significant difference in the average abnormal return on Indonesia’s announcement as a development country.